Sejarah Persempadanan Kelantan-Patani: Kesannya kepada Evolusi Ketamadunan Islam dan Politi Melayu Semenanjung : The History of Kelantan-Patani Border Delineation: Its Effects to the Islamic Civilisational Evolution of Malay Peninsula Polities - Alias, Nizamuddin; Ahamat, Haniff (Journal of Al-Tamaddun, 2023)
The Kelantan-Patani border was determined through the Anglo-Siamese Treaty 1909. The treaty changed the previous border of the two states by giving the west bank of Golok River to Thailand (Patani), while giving the district of Jeli to Malaysia (Kelantan). This article intends to study a few objectives. They are inter alia, firstly to study the importance of rivers to Malay polities in general and to see its relations to Golok River. Secondly, this article studies the western part of Kelantan border before the 1909 treaty. Thirdly, this article also explains the border delineation process which was determined by the Anglo-Siamese 1909 Treaty. Fourthly, the article analyses the effects of Kelantan-Patani border delineation to the evolution of Malay Peninsula polities. The method of the research involves black letter law method and legal history method. Documents analysed include the Anglo-Siamese Treaty 1909, books, historical documents related to the negotiations in Kelantan-Patani border delineation process, as well as diplomatic correspondence between the British and Siamese officials. The study finds that the reorganisation process done by Britain and Siam did not only comprise the determination, acquisition and territorial losses by both powers, but also isolated Patani from other Malay Peninsula polities. Moreover, it brought unintended consequences due to the British failure in considering Malay civilisation and cultural factors in the process of determining the border delineation.